2010
DOI: 10.1038/ajg.2010.104
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Esophageal Stenting in the Management of Benign Perforations

Abstract: In patients with a benign esophageal perforation, temporary stent therapy is effective and provides a good alternative to surgery. Complications due to stent removal can be prevented by removal of the prosthesis within 6 weeks after insertion, without compromising the efficacy of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 37 publications
2
75
1
3
Order By: Relevance
“…In 2009, Leers et al reported a series of 15 patients treated with self-expanding metal stents, achieving a success rate of 87% without further intervention (23). Van Heel and colleagues also reported a series of 33 patients with an esophageal perforation treated with a variety of stent types in 2010 (24). Despite the stent sealing the perforation in 32 (97%) patients, 4 (12%) patients eventually required esophagectomy because of a recurrent leak or complications of removing the stent.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Leers et al reported a series of 15 patients treated with self-expanding metal stents, achieving a success rate of 87% without further intervention (23). Van Heel and colleagues also reported a series of 33 patients with an esophageal perforation treated with a variety of stent types in 2010 (24). Despite the stent sealing the perforation in 32 (97%) patients, 4 (12%) patients eventually required esophagectomy because of a recurrent leak or complications of removing the stent.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to the literature, the etiology of esophagus perforation was mainly iatrogenic in our database [6]. Factors increasing the risk of iatrogenic perforation include preexisting diseases such as large hiatal hernia, vigorous achalasia, or…”
Section: Discussionmentioning
confidence: 85%
“…Treatment options include operative and nonoperative managements such as stent implantation [9,10]. The best indication of stent implantations is small perforations diagnosed early without any signs of sepsis that have an adequate distance to the upper and lower esophageal sphincters for a sufficient sealing [6]. Stent explantation is recommended after 4-6 weeks [6,11].…”
Section: Early Presentation <24hmentioning
confidence: 99%
See 2 more Smart Citations